TERAPI FARMAKOLOGI COVID-19 PADA KEHAMILAN - Mutia Fatmawati Sitorus (Jurnal Kesehatan Rajawali, 2021)
Coronavirus Disease 2019 (COVID-19) is still a major health problem, not only in Indonesia but in the world. Until the time this article was written, COVID-19 cases were still increasing in various parts of the world. The clinical manifestations of COVID-19 vary, with most patients having respiratory symptoms. Prompt management is expected to save the patient's life, especially in vulnerable populations such as pregnancy. This study aims to provide a general description of the consideration of pharmacological therapy in pregnant woman with COVID-19. The type of review is in the form of a literature review of several COVID-19 articles using the PubMed and Google Scholar databases. The results of the study show that pharmacological interventions commonly given related to COVID-19 in pregnancy include antiviral therapy (remdesivir, lopinavir/ritonavir), antibiotics, corticosteroids (dexamethasone, betamethasone), thromboembolic (low molecular weight heparin/LMWH), and immunomodulators (convalescent plasma, tocilizumab, immunoglobulin G, etc.).